Lebesgue quadratic stochastic operators on segment [0,1] - Ganikhodjaev, Nasir; Hamzah, Nur Zatul Akmar (2015)
In this paper, we introduce new class of Lebesgue quadratic stochastic operators on segment [0,1]. Then, we investigate their limit behaviors and show that these operators are regular transformations.